Clinical Profile of Diabetes Mellitus in Children and Adolescents under Eighteen Years of Age - Mohsin, Fauzia; Zabeen, Bedowra; Zinnat, Rahelee; Azad, Kishwar; Nahar, Nazmun (Ibrahim Medical College Journal, 2008)
A total number of 125 patients with diabetes mellitus (DM) under eighteen years of age were admitted in the Paediartic department of BIRDEM hospital between January 2001 to October 2002. Eighty-eight patients (71%) were newly detected. Female to male ratio was 3:1. Out of the total admission 38 (30.4%) patients had type 1 DM (group 1), 37 (29.6%) patients had fibrocalculous pancreatic FCPD diabetes (group II), 48 (38.4%) patient had malnutrition modulated diabetes mellitus MMDM (group III) and 2 (1.6%) patients had type 2. Mean age of onset was 9±3.9 yrs in group I and 13±2.3 yrs in group II and group III. All groups had very high glucose and HbA1c value at presentation. The mean fasting glucose (mmol/l) was 19±7.14, 22.39±9 and 19.54±7.9 in group I, group II and group III respectively. The Mean HbA1c (%) value in the three groups was 14.4±2.7, 16.72±2.26 and 15.27±3.05 respectively. FCPD patients had poorest glycaemic status. Acute complications were more common in type 1 patients. Twelve (31.5%) patients had diabetic ketoatin DKA and two (5%) patients had hypoglycaemia in group I. Chronic complications were present in all three groups. MMDM patients had highest rate of complications. which was present in 2.6%, 21.6% and 33.3% patients in group I, group II and group III respectively. The rate of microalbuminuria was 5.3%. 10.8% and 18.8% in the three groups respectively. The rate of neuropathy was 2.6%, 16.2% and 20.8% in the three groups respectively. Among the associated problems skin infection, pulmonary tuberculosis and bilateral parotid swelling were common. Malnutrition was present in 66%, 86% and 100% in group I, group II and group III respectively. Majority (50% in group I, 91.6% in group II and 100% in group III) of our patients came from poor socio-economic background. Ibrahim Med. Coll. J. 2007; 1(1): 11-15 Key words: Diabetes mellitus doi: 10.3329/imcj.v1i1.2889